Variasi Substrat dan Waktu pada Fermentasi Tapai: Tinjauan Narasi - Prasetyo, Angga; Rasmiyana, Rasmiyana (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2025)
Tapai is a fermented food product made from various substrates, such as cassava, glutinous rice, taro, corn, banana, and purple sweet potato. This study uses a narrative review method by providing a non-systematic summary and analyzing a specific topic. The topic analyzed is research findings related to the ingredients that have been processed into tapai products and the effect of fermentation time on tapai. The fermentation process of tapai involves bacteria and yeast, which both play a role in converting carbohydrates in the substrate into simple sugars, alcohol, and organic acids. This fermentation process increases the content of bioactive compounds, such as phenolic compounds and flavonoids, which have health benefits, including enhancing the immune system and antioxidant activity. Fermentation time affects the sensory quality and nutritional content of tapai. Based on this narrative review, the optimal fermentation of tapai occurs within a time range of 48 to 72 hours, where significant changes occur in taste, aroma, texture, and nutritional content, such as a reduction in fat content and an increase in protein content. Different tapai substrates produce distinct microorganisms and chemical compounds, which contribute to the variation in product quality.